Instilling Moderation: Transforming Religious Education in Madrasah Aliyah - Rusmana, Dadan; Gunawan, Heri; Martiningsih, Dwi (SCAD Independent, 2025)
Religious moderation serves as a pillar of unity and diversity, a glue and unifier of the nation. It helps prevent conflicts that may arise due to differences in religious beliefs and practices. This study uses content analysis and survey methods, with data collection through interview techniques, literature studies, and surveys of teachers and students at the Madrasah Aliyah in the city of Bandung. This study aims to determine the moderation material in the Quran Hadith book and the responses of teachers and students to the application of learning materials based on religious moderation. The results of the study indicate that the religious moderation education material at Madrasah Aliyah in the Quran Hadith textbook is more associated with the values contained in the holy texts, as well as the understanding and practice of moderation based on the teachings of the Quran and Sunnah, covering several themes, namely balance (tawazun), religious tolerance (tasamuh), responsible attitude, and maintaining trust. The concept of religious moderation is easy to understand and implement in life as students’ attitudes are more open to accepting opinions and respecting differences. One effort to instill an attitude of religious moderation among students can be made by integrating the values of religious moderation into the teaching materials of the Quran and Hadith.